2020
DOI: 10.1149/1945-7111/ab6b08
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of an Efficient Ni–Fe–Co Based Oxygen Evolution Reaction Electrocatalyst

Abstract: Electrolytic water splitting offers energy storage and conversion opportunities, yet the slow kinetics of the oxygen evolution reaction requires the incorporation of catalytic materials. Herein, we present a facile method for the synthesis of a low-cost Ni-Fe-Co material that efficiently catalyzes the oxygen evolution reaction. A mixed transition metal electrocatalyst was synthesized using a nickel-plated iron substrate and a low concentration cobalt reagent. The catalyst was able to achieve competitive curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 114 publications
(204 reference statements)
1
11
0
Order By: Relevance
“…The rFNCO electrode also exhibits a very low overpotential of 246 mV even at a very high current density of 100 mA cm –2 . It is worth noting that the catalytic OER activity achieved by the rFNCO electrode is comparable or even superior to that of the recently reported state-of-the-art non-precious-metal oxide-based electrocatalysts (Figure c). Furthermore, the intrinsic activity of the samples was assessed by normalizing the geometrical current density using the corresponding ECSA, as shown in ECSA-based LSV curves (Figure S7). The normalized LSV curves revealed that the intrinsic OER catalytic activity of the samples followed the same order of rFNCO > FNCO > NCO, as observed in the geometrical area-based voltammograms.…”
Section: Results and Discussionmentioning
confidence: 60%
“…The rFNCO electrode also exhibits a very low overpotential of 246 mV even at a very high current density of 100 mA cm –2 . It is worth noting that the catalytic OER activity achieved by the rFNCO electrode is comparable or even superior to that of the recently reported state-of-the-art non-precious-metal oxide-based electrocatalysts (Figure c). Furthermore, the intrinsic activity of the samples was assessed by normalizing the geometrical current density using the corresponding ECSA, as shown in ECSA-based LSV curves (Figure S7). The normalized LSV curves revealed that the intrinsic OER catalytic activity of the samples followed the same order of rFNCO > FNCO > NCO, as observed in the geometrical area-based voltammograms.…”
Section: Results and Discussionmentioning
confidence: 60%
“…The overall efficiency of the methanol oxidation can be determined by 50,53‐57 : η=itioerit×100%, where i t is the overall current density during electrolysis of methanol. The overall efficiency of the electrocatalytic conversion of methanol is observed to be ~60% in the present work.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the roughness factors (RFs) for different carbon containing copper‐cobalt oxide structures have been evaluated using 56,57 : RF=Electrochemically active surface areas0.25em()ECSAGeometric surface area of the electrode. …”
Section: Resultsmentioning
confidence: 99%
“…Many other transition metals have been substituted into NiOOH, forming bimetallic LDH OER catalysts, such as Co, , V, Mn, Cr, Zn . The introduction of an additional or even two additional transition metals into NiFe-LDH resulted in improved OER activity. The design of the catalysts can be eased by a Sabatier-type analysis, where the difference between the adsorption energies of *O and *OH serves as a descriptor for OER activity trends.…”
Section: Electrochemical Behavior Of Layered Double Hydroxidesmentioning
confidence: 99%